Female Staffs’ Acceptance and Use of Self-Service System: Review of the Current Trend at Saudi Arabian Ministry of Education: قبول المعلمات والموظفين لاستخدام نظام فارس للخدمة الذاتية: دراسة حالة على وزارة التربية والتعليم السعودية - Sanaa Khalid Al-Motairi - Majed Abdulaziz Al-Braithen (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2019)
: In the recent years, Saudi Arabia has put tremendous efforts to move to e-government. Ministry of Education at Saudi Arabia moved to e-government where it launched Faris Self Service System to enable the teachers benefit from the Ministry services easily. Faris Self Service System is an integrated web-based system used to provide various services to teachers, administrators through an online integrated electronic system (MOE, 2018). The aim of the current study was to evaluate the female administrative staff’s acceptance and use of Faris Self Service System where semi-structured interviews were conducted with 17 of the female staff’s working at the ministry of education in Saudi Arabia. Results of the study revealed that some of the female teachers and administrative staff have rated the Faris program favorably, while some other rated the program negatively and they just use it because they are obliged to do so. This suggests that the Saudi Ministry of Education who has sought to implement the electronic self-service program did well in taking the whole nation into account when formulating their strategy, and ideally focused on improving their operations in order to deliver better service to the female staffs. Finally, the results revealed the need to handle the system drawback and fix them to meet the needs of the female teachers and administrative staff.